Aboge Sebagai Siklus Awal Tahun Menyalahi Sunnatullah - Ramadhan, Rizal; Izzuddin, Ahmad; Mahsun (Universitas Islam Negeri Mataram, 2023)
The Javanese Islamic Aboge calendar is one of the local Indonesian calendars whose calculations are static and standard. The Javanese calendar is a special calendar because it is a blend of Islamic culture and Javanese Hindu-Buddhist culture whose calculations are based on the moon around the sun. Astronomically, the Javanese calendar is classified as a mathematical calendar, while the Hijri calendar is an astronomical calendar. Methodologically this paper is a Research Library where the data collected comes from library sources that are considered representatively related to the object of this study. This paper is descriptive-analytical, where this paper will explain and explain the truth and error of a fact. Then also analytically developed in a balanced manner by looking at the advantages and disadvantages of the object under study. According to the reckoning rukyah discourse, the Aboge system which includes 'urfi reckoning is no longer relevant to what is required by syara' and cannot be used in determining the beginning of the Lunar month related to the implementation of worship (determination of Ramadan fasting and holidays). Because according to this system, the age of Sha'ban remains 29 days while the month of Ramadan also remains 30 days.